2023
DOI: 10.21037/jtd-22-1865
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional indices for screening sarcopenia before adult cardiac surgery

Abstract: Background Malnutrition can increase and exacerbate sarcopenia, and preoperative nutritional indices could have potential use as screening tools for sarcopenia in all patients, not only those with limited activity. Muscle strengths, such as grip strength, chair stand test, are used to screen for sarcopenia, but these measurements are time-consuming and cannot be applied to all patients. This retrospective study was conducted to determine whether nutritional indices can predict the presence of sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
(41 reference statements)
1
3
0
Order By: Relevance
“… 23 , 40 , 43 Similarly, the NRI has been identified as an independent predictor of sarcopenia presence and survival in cancer and surgery patients, suggesting it could serve as an alternative means of malnutrition assessment for populations with sarcopenia. 22 , 44 Our study confirmed NRI as a clinical indicator for independently predicting sarcopenia incidence, with a good predictive value, especially in middle-aged and elderly males. Compared to other derived inflammatory and nutritional biomarkers, NRI appears to be more promising for further study.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“… 23 , 40 , 43 Similarly, the NRI has been identified as an independent predictor of sarcopenia presence and survival in cancer and surgery patients, suggesting it could serve as an alternative means of malnutrition assessment for populations with sarcopenia. 22 , 44 Our study confirmed NRI as a clinical indicator for independently predicting sarcopenia incidence, with a good predictive value, especially in middle-aged and elderly males. Compared to other derived inflammatory and nutritional biomarkers, NRI appears to be more promising for further study.…”
Section: Discussionsupporting
confidence: 73%
“… 38 To identify a biomarker that can effectively and efficiently screen for sarcopenia in the middle-aged and elderly population, we introduced inflammatory and nutritional biomarkers (PIV, ALI, PNI, and NRI/GNRI) that are widely used to evaluate therapeutic outcomes and predict prognosis in cancer patients with sarcopenia. 20 , 22 , 23 , 39 , 40 NRI, which combines albumin and weight loss, has been commonly utilized as an index of malnutrition in hospitalized adults. Compared to previous studies, our study provides a more comprehensive and scientifically rigorous analysis due to the relatively larger sample size and inclusion of indexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations